The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1108/itse-01-2022-0007
|View full text |Cite
|
Sign up to set email alerts
|

Visual literacy shown through a magnifying lens by high school students

Abstract: Purpose The purpose of this study is to evaluate student visual literacy skills using the newly designed visual literacy framework and visual literacy (VL) scale. Design/methodology/approach It includes a newly designed framework, a self-reporting questionnaire and a scale to evaluate an individual's VL skills and overall competency. The self-reporting questionnaire consists of 13 items with a five-point Likert scale. Findings The newly developed VL skill scale assessed the Fiji students’ competency (i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Some DL competences are prerequisites for other DL competences. Eventually, almost everyone should develop the entire complex of them at a certain age, with or without the assistance of the education system, in order to learn and work successfully in technology‐enhanced environments (Jin et al, 2020; Reddy et al, 2022d). Our findings showed a very low actual performance of both age groups with a relatively small increase in the performance of middle school students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some DL competences are prerequisites for other DL competences. Eventually, almost everyone should develop the entire complex of them at a certain age, with or without the assistance of the education system, in order to learn and work successfully in technology‐enhanced environments (Jin et al, 2020; Reddy et al, 2022d). Our findings showed a very low actual performance of both age groups with a relatively small increase in the performance of middle school students.…”
Section: Discussionmentioning
confidence: 99%
“…In Porat et al's (2018) study, which examined Hebrew‐speaking students, medium correlation was found between branching and information literacies, suggesting that students who navigate effectively in digital environments are successful in finding relevant digital information and evaluating its credibility. The photo‐visual skill helps users to intuitively and freely ‘read’ and understand instructions and messages (Eshet‐Alkalai, 2012; Opperman, 2002; Reddy et al, 2022d). These differences between the findings of previous studies and the current one can be explained by Hofstede's dimensional paradigm (Hofstede, 1980, 2001, 2011) regarding the difference between cultures which related to the power distance dimension.…”
Section: Discussionmentioning
confidence: 99%
“…This deficit impedes their ability to utilize digital technologies for everyday tasks and access online services [ 6 ]. As digital technologies transform textual information more and more into visual media so traditional skills like visual literacy are changing and becoming crucial part of digital literacy [ 7 ], but all other related literacies are changing as well The realm of digital literacy becomes increasingly challenging to definitively define with the continuous emergence of new digital technologies, tools, and literacies. The concept of digital literacy has roots dating back to the 1960s, and it has evolved over time.…”
Section: The Role Of the Digital Literacy In Provision Of Healthcare ...mentioning
confidence: 99%
“…It determines how one uses the internet, such as using the internet to engage in capital-enhancing activities including learning and obtaining career support, offsetting the influence of their socioeconomic background in social capital accumulation (Chan, 2022;Van Deursen et al, 2015). Therefore, it is considered as an essential skill in the 21st century, to help one lead their personal lives "from carrying out personal tasks to education to being employed" (Reddy et al, 2021, p. 5536;Reddy et al, 2022c). Although the current generation is known as "digital natives" because they get used to the internet and technologies (Prensky, 2001, p. 1;Rainie, 2006), they might not be as digitally proficient as they appear to be (Reddy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is considered as an essential skill in the 21st century, to help one lead their personal lives “from carrying out personal tasks to education to being employed” (Reddy et al. , 2021, p. 5536; Reddy et al. , 2022c).…”
Section: Introductionmentioning
confidence: 99%